2021
DOI: 10.1111/add.15360
|View full text |Cite
|
Sign up to set email alerts
|

Illicit drug use and oral health

Abstract: People with drug use disorders (PWDUD) have elevated prevalence of oral diseases, in particular dental caries (tooth decay), periodontal (gum) disease and xerostomia (dry mouth). When left untreated, these oral health conditions may progress and lead to tooth ache, abscesses and tooth loss, and in turn to poor chewing functioning and digestion, dental aesthetic problems, and reduced wellbeing. Illicit drug use may per se cause xerostomia, which in turn increases vulnerability for dental caries; however, the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 78 publications
1
30
0
Order By: Relevance
“…Risk factors were assessed based upon the prior month as recall period for risk factors in lifestyle in general, smoking, alcohol, illicit drugs, antipsychotic medication and consumption of sugary food/drinks (Kisely et al, 2011 , 2015 ; Kuipers et al, 2018 ; McCreadie et al, 2004b ; Rossow, 2020 ). Risk factors were scored dichotomously (present or absent).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Risk factors were assessed based upon the prior month as recall period for risk factors in lifestyle in general, smoking, alcohol, illicit drugs, antipsychotic medication and consumption of sugary food/drinks (Kisely et al, 2011 , 2015 ; Kuipers et al, 2018 ; McCreadie et al, 2004b ; Rossow, 2020 ). Risk factors were scored dichotomously (present or absent).…”
Section: Methodsmentioning
confidence: 99%
“…smoking, using alcohol or illicit drugs), side effects (e.g. xerostomia) or (antipsychotic) medication, and consumption of sugary food/drinks (Kisely et al, 2015 ; Kuipers et al, 2018 ; McCreadie et al, 2004a ; Rossow, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study amongst homeless injecting substance users in USA found that although 63 % reported a need for oral health care in the past six months, only 27 % of them had sought care [19]. Studies show that lack of financial resources is an important factor for low prioritisation of oral health among patient with SUD [20]. However, in most counties in Norway, oral health care service are free of charge for patients in OMT and people with SUD.…”
Section: Introductionmentioning
confidence: 99%
“…The current study aim to examine OMT patients' and DHWs' perceptions of barriers related to the use of oral health care services among OMT patients. Considering that cost is often perceived one of the main barriers to (the) use of oral health care services [20], this article explores the reasons for low use of oral health care services in a context where this barrier has been removed; i.e. in Norway.…”
Section: Introductionmentioning
confidence: 99%